Strategic approachesfor sustainable development of smallholder cocoa plantations in North Luwu Regency, South Sulawesi - Abdullah Abdullah; Abdul Haris; Dadan Hidayat; Hamed Norolla Bakheet Ali (Universitas Trunojoyo Madura, 2025)
North Luwu Regency is the largest cocoa producer in South Sulawesi Province; however, the productivity and quality of its cocoa products are still relatively low. The challenges faced are very complex, involving both internal and external factors. To overcome these challenges, a comprehensive approach with the right strategy is needed.The goal is to realize sustainable community cocoa plantation development.This study aims to formulate alternative strategies for sustainable community cocoa plantation development in North Luwu Regency. The study employs Internal and External Factor Evaluations (IFE and EFE), followed by SWOT analysis, to assess management practices in community-based cocoa plantations. The results indicate that the sustainability of community cocoa plantations is threatened by internal weaknesses and significant external threats. This study proposes a defensive strategy that includes the identification and mitigation of internal weaknesses and the proactive anticipation of external threats. The implementation of this strategy necessitates collaborative and coordinated efforts among local governments, which function as the primary leaders in the upstream sector, cocoa stakeholders, who serve as leaders in the downstream sector, and farmers, who act as the primary agents.